2015
DOI: 10.1007/s00221-015-4439-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial gradients of oculomotor inhibition of return in deaf and normal adults

Abstract: We explored the effect of deafness on the spatial (gradient) and temporal (decay) properties of oculomotor inhibition of return (IOR) using a task developed by Vaughan (Theoretical and applied aspects of eye movement research. Elsevier, North Holland, pp 143-150, 1984) in which participants made a sequence of saccades to carefully placed targets . Unlike IOR tasks in which ignored cues are used to explore the aftereffects of covert orienting, this task better approximates real-world behavior in which participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…An unusual effect in the SRTs of Experiment 1 was that they were equally slow, irrespective of whether the target location or hemifield repeated. Why weren't responses especially slow when the target location repeated, as was shown by previous eye movement research in target-target cueing paradigms (e.g., Jayaraman, Klein, Hilchey, Patil, & Mishra, 2016)? It could still be the case that performing a fine-grained perceptual analysis of the target required focal attention, which produced some amount of facilitation at the prior target location that added with any inhibition that was generated by orienting to it, as was suggested by Maljkovic and Nakayama (1996).…”
Section: Methodsmentioning
confidence: 82%
“…An unusual effect in the SRTs of Experiment 1 was that they were equally slow, irrespective of whether the target location or hemifield repeated. Why weren't responses especially slow when the target location repeated, as was shown by previous eye movement research in target-target cueing paradigms (e.g., Jayaraman, Klein, Hilchey, Patil, & Mishra, 2016)? It could still be the case that performing a fine-grained perceptual analysis of the target required focal attention, which produced some amount of facilitation at the prior target location that added with any inhibition that was generated by orienting to it, as was suggested by Maljkovic and Nakayama (1996).…”
Section: Methodsmentioning
confidence: 82%
“…We conclude this because in this context, as in when eye movements are required toward cues or targets, IOR can be measured by manual and saccadic responses to arrows at fixation (Hilchey, Dohmen, Crowder, & Klein, 2016; Taylor & Klein, 2000). Second, and more compellingly, there are many eye movement studies without placeholder objects that demonstrate IOR (i.e., stimuli are simply presented against a uniform greyscale or black background; e.g., Abrams & Dobkin, 1994a, 1994b; Christie, Hilchey, & Klein, 2013; Hilchey, Klein, Satel, & Wang, 2012; Jayaraman, Klein, Hilchey, Patil, & Mishra, 2016; MathĂ´t & Theeuwes, 2010; Pertzov, Zohary, & Avidan, 2010; Vaughan, 1984; Wang, Satel, Hilchey, & Klein, 2012; Watanabe, 2001).…”
Section: Experiments 2a and 2bmentioning
confidence: 99%
“…IOR manifested in prolonged response times (RTs) to targets at the cued location and, importantly, RTs decreased as the cue-target distance increased, showing a clear spatial gradient for IOR. Other work suggests that this IOR gradient is unaffected by response modality (manual or saccadic; Christie et al, 2013;Wang et al, 2014) and can also be observed at previously foveated locations (Vaughan, 1984;Jayaraman, Klein, Hilchey, Patil, & Mishra, 2015). 1 In cueing tasks, the magnitude of IOR reaches its maximum about 300-500 ms following cue onset, and then steadily decreases (for reviews, see Klein, 2000;Samuel & Kat, 2003).…”
Section: Introductionmentioning
confidence: 97%